Difficulties in Translating Appetite Sensations Effect of Turmeric-Based Beverage When Given Prior to Isoenergetic Medium- or High-Fat Meals in Healthy Subjects - Zanzer, Yoghatama; Batista, Ângela; Dougkas, Anestis; Tovar, Juscelino; Granfeldt, Yvonne; Östman, Elin (Nutrients, 2019)
The established effect of turmeric and its curcuminoids on appetite sensations was previously shown to be mediated by gut hormones release. In in vitro and preclinical studies, curcumin was shown to induce GLP-1 secretion and improve postprandial glycemia. In humans, consumption of 220 mL turmeric-based beverage (TUR, containing 185 mg gallic acid equivalents (GAE)) prior to white wheat bread (WWB, 50 g available carbohydrate) reduced early postprandial glucose levels and induced peptide tyrosine–tyrosine (PYY) release, as well as lowered ‘desire to eat’ and ‘prospective consumption’ in a postprandial setting, compared to control. In the present study, 12 healthy participants (5 men, 7 women) were admitted. An identical beverage was given and consumed prior to isoenergetic (423 kcal) medium-fat (MF) or high-fat (HF) meals. Appetite sensations including perceived ‘hunger’, ‘desire to eat’, ‘satiety’, ‘fullness’, ‘prospective consumption’, and ‘thirst’ were measured using visual analogue scales. MF induced 18% (p = 0.039) higher ‘satiety’ compared to HF. TUR consumption prior to either MF or HF did not modulate the perceived appetite sensations. Whether macronutrient-induced appetite sensations override the actual turmeric effects warrants further investigation.